Implementation of Immigration Control Against Traditional Border Crossers in The Border Area of The Republic of Indonesia And Papua New Guenea in Merauke - Julianto Jover Jotam Kalalo; Samingun Samingun (Fakultas Hukum Universitas Mataram, 2021)
The Republic of Indonesia and Papua New Guinea are land and sea neighbors whose borders are located in the Papua Province in the eastern part of Indonesia. The border area consists of Census Divisions within Papua New Guinea and border villages within the Republic of Indonesia as defined, where the border is part of the boundaries of the Census Divisions and the border villages. State border areas are the main manifestation and have an important role in determining border areas, utilization of natural resources, security and territorial integrity. Supervision is very important because it is to maintain and supervise the presence of foreign nationals who enter with all kinds of activities while they are in Indonesian territory until they depart or leave Indonesian territory. The purpose of the study was to determine the process of immigration control of traditional border crossers in the border areas of Indonesia and PNG in Merauke district. The problem approach used is the empirical juridical approach, which is a research approach carried out to analyze the extent to which the effectiveness of a regulation / legislation or law in society, the research location in Merauke Regency, and the Sota Cross-border Post there was a process of traditional crossing of Indonesian citizens and Papuan New Guinea citizens. This study is intended to see how the application of Indonesian legal regulations, especially immigration in traditional border crossers in border areas in Merauke. In the application of Indonesian laws and regulations, the immigration process uses immigration laws and also with the existence of mutual agreements between Indonesian countries and Papua New Guinea. the implementation of immigration checks uses several mechanisms, namely administration, and the field is carried out by immigration officials in the work area of the Class II Immigration Office of TPI Merauke.